2006
DOI: 10.1152/ajplung.00271.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococci induced TLR- and Rac1-dependent NF-κB-recruitment to the IL-8 promoter in lung epithelial cells

Abstract: induced TLR-and Rac1-dependent NF-B-recruitment to the IL-8 promoter in lung epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
88
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 58 publications
7
88
2
3
Order By: Relevance
“…SP3 may have a similarly low binding affinity to MLE-15 cells, possibly contributing to the present lack of SP3-induced RelA activation. Although others have demonstrated SP3-induced NF-B activation in bronchial epithelial cells (54,57,58), our current data argue against this serotype of S. pneumoniae as a significant stimulus for RelA activation in alveolar epithelial cells during pneumococcal pneumonia.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…SP3 may have a similarly low binding affinity to MLE-15 cells, possibly contributing to the present lack of SP3-induced RelA activation. Although others have demonstrated SP3-induced NF-B activation in bronchial epithelial cells (54,57,58), our current data argue against this serotype of S. pneumoniae as a significant stimulus for RelA activation in alveolar epithelial cells during pneumococcal pneumonia.…”
Section: Discussioncontrasting
confidence: 84%
“…TLR2 is expressed on the surface of type II alveolar epithelial cells (52,53) and has been shown to permit S. pneumoniae-induced NF-B activation in this cell type (54,55). Interestingly, SP3 failed to induce RelA nuclear translocation in our current studies, regardless of dose or timing.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that TLR2 is the main pattern recognition receptor for live S. pneumoniae, while pneumolysin is predominantly recognized by TLR4. This model is supported by the recent work of Schmeck et al (45) who observed that live S. pneumoniae-induced NF-B activity is exclusively dependent on TLR2 whereas pneumolysin-induced NF-B activity is exclusively dependent on TLR4. Their results are congruent with our finding that pneumolysin-induced activation of IKK-ERK signaling is mainly TLR4-dependent.…”
Section: Discussionsupporting
confidence: 60%
“…Numerous in vivo and in vitro studies have examined the signaling events required for activation of respiratory epithelial cells by microbes (3,(8)(9)(10)(11). As in immune cells, the cellular response of epithelial cells activated by TLRs can be MyD88-dependent or -independent (12).…”
mentioning
confidence: 99%